TINJAUAN BAURAN PEMASARAN 7P TABUNGAN BTN BISNIS PADA BANK TABUNGAN NEGARA - Tasia Agnesia (2023)
The newest product from Bank BTN is the BTN Bisnis Savings product which was launched at the end of March 2022, BTN Bisnis Savings certainly does market and has existing strategies, Bank Tabungan Negara uses the 7P Marketing Mix for its BTN Business Savings products. This writing aims to find out how Bank BTN implements the 7P marketing mix on Business BTN Savings and to find out what are the obstacles in implementing the 7P marketing mix on Business BTN Savings products. The research method used is using qualitative descriptive techniques and for data collection techniques using interview techniques. For the population and sample in this study, namely employees of Bank BTN Melawai Branch and customers of Bank BTN Bisnis. Based on the results of the research, it shows that the National Savings Bank applies the 7P Marketing Mix well in BTN Business Savings products to increase the number of customers or business people.